MENINGKATKAN PRESTASI BELAJAR SISWA SMA PADA MATERI GELOMBANG BUNYI MENGGUNAKAN STRATEGI MULTIPLE INTELLIGENCES - Vantri Pieter Kelelufna; Agustinus Lia Masan (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2019)
A person has compound intelligence is the foundation for improving cognitive, affective and psychomotor learning achievements. Individually, the multiple intelligences that a person has are more than one or heterogeneous, so that abilities may be developed with some compound intelligence. The method of study used is descriptive research that is intended to give a description of symptoms, events and actual circumstances, in this case would clearly depict a student has description of sound wave material using a compound wave method. Before student obtain treatment of sound wave material using a compound intelligence strategy, the student mastery level was still very low, but when given the treatment with the compound intelligence strategy the student mastery level experienced improvement.